Interplay between autophagy and coronavirus: autophagy mechanism - Nikolina Elez-Burnjaković; Ajla Smajlović; Milena Dubravac Tanasković (Биомедицинска истраживања, 2023)
Regardless of the fascinating progress of humanity, biotechnology and medicine, the outbreak of the global pandemic of the SARS-CoV-2 virus has shown us that we are just as vulnerable as in previous eras when communicable diseases decimated the world’s population. But the discoveries made so far at the molecular level allow us to connect knowledge interdisciplinary and find solutions and therapeutic strategies where there seems to be no link. It was the previous coronavirus infections that served as a homologous model for finding the connection between the SARS-CoV-2 virus and autophagy. Autophagy, a conserved universal process of all eukaryotic cells responsible for cell survival under stressful circumstances, has been shown to play a significant role in viral invasions. It contributes to both direct and indirect antiviral responses such the elimination of viruses, the presentation of their antigens, and the reduction of inflammatory responses. The autophagy machinery of host cells can, however, be suppressed, evaded, or used by viruses to their benefit. Therefore, autophagy has an ambiguous role in coronavirus-related infections, especially in COVID-19.
Keywords: COVID-19; pandemic; autophagy; SARS-CoV-2 virus